NMDA Receptor Antagonists Increase the Release of GLP-1 From Gut Endocrine Cells - Cyranka, Malgorzata; Monfeuga, Thomas; Vedovato, Natascia; Larabee, Chelsea M; Chandran, Anandhakumar; Toledo, Enrique M; de Wet, Heidi (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) remains one of the most pressing health issues facing modern society. Several antidiabetic drugs are currently in clinical use to treat hyperglycaemia, but there is a need for new treatments that effectively restore pancreatic islet function in patients. Recent studies reported that both murine and human pancreatic islets exhibit enhanced insulin release and -cell viability in response to N-methyl-D-aspartate (NMDA) receptor antagonists. Furthermore, oral administration of dextromethorphan, an over-the-counter NMDA receptor antagonist, to diabetic patients in a small clinical trial showed improved glucose tolerance and increased insulin release. However, the effects of NMDA receptor antagonists on the secretion of the incretin hormone GLP-1 was not tested, and nothing is known regarding how NMDA receptor antagonists may alter the secretion of gut hormones. This study demonstrates for the first time that, similar to -cells, the NMDA receptor antagonist MK-801 increase the release of GLP-1 from a murine L-cell enteroendocrine model cell line, GLUTag cells. Furthermore, we report the 3’ mRNA expression profiling of GLUTag cells, with a specific focus on glutamate-activated receptors and show that this cell line is a good model for the investigation of NMDA receptor function. We conclude that if NMDA receptor antagonists are to be pursued as an alternative, orally administered treatment for T2DM, it is essential that the effects of these drugs on the release of gut hormones, and specifically the incretin hormones, are fully investigated.